Research of compositions of amino acids, fatty acids and minerals in meat pate with addition of meat-and-bone paste - B. K. Kabdylzhar; A. K. Kakimov; Zh. S. Yessimbekov; G. V. Gurinovich; A. K. Suychinov (Теория и практика переработки мяса)
This article analyses the nutritional value of meat pate produced with the addition of meat-and-bone paste obtained from chicken bones. In the test samples of the pate, 20% of the poultry meat was replaced with the meat-and-bone paste. The comparative characteristic of the chemical, amino acid, fatty acid and mineral compositions of meat pate is given in the article. The comparative analysis of the nutritional value of meat pate showed that the addition of meat-and-bone paste decreases the moisture content by 0.23%, fat content by 1.22%, and increased the protein content (by 0.52%). In the test sample of the product the proportion of minerals increased significantly from 1.3% to 2.23% compared to the control sample. In terms of amino acid composition, the addition of meat-andbone paste up to 20% instead of poultry meat significantly increases the content of amino acids like isoleucine (from 196 mg/100 g to 661 mg/100 g), leucine (from 807 mg/100 g to 1083 mg/100 g), threonine (from 454 mg/100 g to 610 mg/100 g). The test samples of pate, compared with the control samples, contain a higher amount of monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids, including oleic (39.698%) and linoleic (21.546%) acids. The content of the saturated fatty acids (SFA) in the control sample are 37.8%, in the test sample it accounts to 32.9%. According to the mineral composition: the content of calcium is significantly increased in the test sample, (from 268.0 mg/100 g to 480.0 mg/100 g). In general, the addition of meat-and-bone paste made of chicken bones allows fortification the pate with the essential amino acids, mono- and polyunsaturated fatty acids and calcium.